2003
DOI: 10.1088/0264-9381/21/1/018
|View full text |Cite
|
Sign up to set email alerts
|

Quantum singularity of Levi-Civita spacetimes

Abstract: Abstract. Quantum singularities in general relativistic spacetimes are determined by the behavior of quantum test particles. A static spacetime is quantum mechanically singular if the spatial portion of the wave operator is not essentially self-adjoint. Here Weyl's limit point-limit circle criterion is used to determine whether a wave operator is essentially self-adjoint. This test is then applied to scalar wave packets in Levi-Civita spacetimes to help elucidate the physical properties of the spacetimes in te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 18 publications
(66 reference statements)
2
32
0
Order By: Relevance
“…The square integrability condition at infinity is calculated by 13) and it is found that the squared norm f i (r) 2 → ∞. This result indicates that all the asymptotic solutions of the Maxwell's equation do not belong to the Hilbert space.…”
Section: Maxwell Fieldsmentioning
confidence: 99%
“…The square integrability condition at infinity is calculated by 13) and it is found that the squared norm f i (r) 2 → ∞. This result indicates that all the asymptotic solutions of the Maxwell's equation do not belong to the Hilbert space.…”
Section: Maxwell Fieldsmentioning
confidence: 99%
“…(63) do not belong to the Hilbert space H (we refer to the references; [46] for detailed mathematical analysis and [47][48][49][50][51][52][53][54][55][56][57][58][59][60] for applications of the HM approach in different spacetimes). This will be achieved by defining the function space on each t =constant hypersurface as H = { R| R < ∞} with the following norm given for the metric (2):…”
Section: Quantum Singularitiesmentioning
confidence: 99%
“…Studies have been made of the nature of the singularity [49] and of the Dirac equation on the Levi-Civita background [50]. Many papers have considered the matching of the Levi-Civita solution to cylindrical sources, whether fluid bodies, shells or more general sources, e.g.…”
Section: This Suggests That Another Interpretation Is Needed Ifmentioning
confidence: 99%